Prevention of Early Marriage and Stunting through the CARE Program for Adolescents in Raja Ampat, Southwest Papua - Nahdiyah Karimah; Entan Afriannisyah (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2026)
In 2023, Southwest Papua reported a stunting prevalence of 31%. Raja Ampat was identified as the district with the highest contribution to stunting cases in the region. Early marriage accounted for 55% of these cases. This community service initiative aimed to prevent early marriage and stunting through the Comprehend, Ask, Respond, Evaluate (CARE) program for adolescents in Raja Ampat, Southwest Papua. The program involved all 51 third-year students at SMKN 2 Raja Ampat (Vocational High School 2 Raja Ampat). Participants’ knowledge and attitudes regarding early marriage and stunting were measured before and after the intervention using two instruments: an 18-item questionnaire on knowledge of early marriage and stunting and a 20-item questionnaire assessing attitudes toward early marriage. Univariate analysis was conducted to describe participant characteristics, knowledge levels, and attitudes. Bivariate analysis using the Wilcoxon signed-rank test was performed to assess changes in knowledge and attitudes. Data were analyzed using SPSS version 22. The results showed that participants’ knowledge improved significantly after the intervention, with low knowledge decreasing from 90.2% at pretest and 58.8% of participants demonstrating excellent knowledge at posttest (p=0.0001). Participants’ attitudes also changed significantly, from predominantly supporting early marriage at pretest (66.7%) to rejecting it after the intervention (88.2%) (p=0.0001). These findings indicate that the CARE program improved adolescents’ awareness of, and critical attitudes toward, early marriage, adolescent pregnancy, and stunting in a geographically isolated area. However, this evaluation measured only short-term outcomes immediately after the intervention, was conducted in a single school, and did not assess long-term behavioral changes. Overall, the CARE program demonstrates the potential of participatory school-based health education as a community engagement strategy for preventing early marriage and reducing future stunting risks in remote areas such as Raja Ampat.